2019
DOI: 10.5811/westjem.2019.1.39261
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Medicine Research Priorities for Early Intervention for Substance Use Disorders

Abstract: Introduction Patients with substance use disorders (SUDs) frequently seek emergency care, and the emergency department (ED) may be their only point of contact with the healthcare system. While the ED visit has been increasingly recognized as providing opportunity for interventions around substance use, many questions remain. Methods In December 2016 the Coalition on Psychiatric Emergencies (CPE) convened the first Research Consensus Conference on Acute Mental Illness, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…With regard to substance use, more research is needed on screening and intervention for substance use in the ED 29. Indeed, in the period of time that has elapsed since this conference the director of the National Institute of Drug Abuse has made public comments likening the failure of EDs to provide treatment options to patients with SUD as potential “malpractice.”30 In the psychosis workgroup, better methods for screening, measurement, and evaluation of psychosis are needed.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to substance use, more research is needed on screening and intervention for substance use in the ED 29. Indeed, in the period of time that has elapsed since this conference the director of the National Institute of Drug Abuse has made public comments likening the failure of EDs to provide treatment options to patients with SUD as potential “malpractice.”30 In the psychosis workgroup, better methods for screening, measurement, and evaluation of psychosis are needed.…”
Section: Resultsmentioning
confidence: 99%
“…The emergency department visit represents an opportune window to initiate AUD treatment because the ED visit is frequently the only point of contact with the health system for patients with SUD [41]. The ED visit is increasingly recognized as an important point for intervention for patients with SUD [41], and the ED has been shown as an effective venue for MAT programs focused on the treatment of opiate use disorder [8].…”
Section: Discussionmentioning
confidence: 99%
“…The EPs we interviewed engaged in a variety of strategies to help encourage compliance with observation and to reduce harm. Many of these strategies, such as expressing direct, personal concern for patients' well-being, are rooted in establishing a therapeutic alliance, wellsupported by the addiction medicine literature, and in keeping with the foundational ethical principles of beneficence and respecting autonomy (38)(39)(40). Likewise, a significant number of interviewees expressed interest in providing MAT in the ED or reported that they had already made this part of their practice.…”
Section: Discussionmentioning
confidence: 99%